Meningkatkan Literasi dan Numerasi Siswa SDN 1 Satap Sukun Melalui Kegiatan Kampus Mengajar - Fransiska Liliana (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
The Campus Teaching Program at State Elementary School (SDN) 1 Satap Sukun aims to improve students’ literacy and numeracy competencies through guidance from Muhammadiyah Maumere University students. This program is a collaborative initiative between schools and the Maumere Muhammadiyah University which aims to provide guidance and assistance to students in understanding the subject matter in more depth. The approach used in this program involves students being active as tutors for students who need additional help in the areas of literacy and numeracy. This program succeeded in increasing students’ understanding of the subject matter and their learning motivation. From the evaluation results, it was concluded that this program was effective in supporting student competency development. Apart from that, this program also provides valuable experience for students in developing leadership and communication skills. The recommendation from this program is that similar programs can be implemented in more schools to support overall student competency development. In this way, it is hoped that students can achieve their maximum potential in the fields of literacy and numeracy.